Response of Farmer Women Groups To Effectiveness of Aquaponic Systems on Growth and Production of Lettuce (Lactuca sativa L.) - Syaifuddin Syaifuddin; Ainul Hamzah; Buhaerah Buhaerah; Jati Nurcholis (BEST Journal (Biology Education, Sains and Technology), 2022)
Responses of Farm Women Groups on the Effectiveness of Aquaponic Systems on Growth and Production of Lettuce ( Lactuca sativa L.) (supervised by Syaifuddin, Buhaerah and Jati Nurcholis).Aquaponics is a combination of aquaculture (fish farming) and hydroponics (plant cultivation). This study aims to : (1) Determine the effectiveness of the aquaponics system on the growth and production of lettuce ( Lactuca sativa L.). (2) Knowing the response of the female farmer groups to increasing knowledge, attitudes and skills towards the effectiveness of the aquaponic system on the growth and production of lettuce ( Lactuca sativa L.)This study used a randomized block design (RBD) analysis with 4 types of treatment and 3 replications so that there were 12 treatments, namely P0: Control (Without Treatment), P1: 70 liters of well water + 10 catfish seeds aged 4 weeks, P2: 70 liters well water + 20 catfish seeds 4 weeks old, P3: 70 liters of well water + 30 catfish seeds 4 weeks old. The parameters observed were plant height, number of leaves and fresh weight of harvest.The results of the study showed that the treatment of 70 liters of well water + 30 catfish seeds aged 4 weeks was effective in increasing the growth and production of lettuce plants with an average plant height of 22.68 cm, the average number of leaves reaching 10.58 and fresh harvest reached 42.67 grams at the age of 5 weeks after planted. The level of knowledge, attitudes and skills of respondents regarding counseling materials concerning the effectiveness of the aquaponics system on the growth and production of lettuce has increased at the knowledge level increased by 46.00%, the attitude level increased by 26.60% and at the skill level increased by 44.40%